Plasma capric acid concentrations in healthy subjects determined by high-performance liquid chromatography. (September 2015) - Shrestha, Rojeet; Hui, Shu-Ping; Imai, Hiromitsu; Hashimoto, Satoru; Uemura, Naoto; Takeda, Seiji; Fuda, Hirotoshi; Suzuki, Akira; Yamaguchi, Satoshi; Hirano, Ken-ichi; Chiba, Hitoshi
Background: Capric acid (FA10:0, decanoic acid) is a medium-chain fatty acid abundant in tropical oils such as coconut oil, whereas small amounts are present in milk of goat, cow, and human. Orally ingested FA10:0 is transported to the liver and quickly burnt within it. Only few reports are available for FA10:0 concentrations in human plasma. Methods: Fasting (n = 5, male/female = 3/2, age 31 ± 9.3 years old) and non-fasting (n = 106, male/female = 44/62, age 21.9 ± 3.2 years old) blood samples were collected from apparently healthy Japanese volunteers. The total FA10:0 in the plasma were measured by high-performance liquid chromatography after derivatization with 2-nitrophenylhydrazine followed by UV detection. Results: Inter and intra-assay coefficient of variation of FA10:0 assay at three different concentrations ranged in 1.7–3.9 and 1.3–5.4%, respectively, with an analytical recovery of 95.2–104.0%. FA10:0 concentration was below detection limit (0.1 µ mol/L) in each fasting human plasma. FA10:0 was not detected in 50 (47.2%) of 106 non-fasting blood samples, while 29 (27.4%) plasma samples contained FA10:0 less than or equal to 0.5 µ mol/L (0.4 ± 0.1), and 27 (25.5%) contained it at more than 0.5 µ mol/L (0.9 ± 0.3). Conclusion: A half of the non-fasting plasma samples contained detectable FA10:0. This simple, precise, and accurate high-performance liquid chromatography method might be useful for monitoring plasma FA10:0 during medium-chain triglycerides therapy.